2008
DOI: 10.1021/jp8020968
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium Nitrate−Polymer Glasses: A New Concept for Phase and Thermal Stabilization of Ammonium Nitrate

Abstract: Dissolving of ammonium nitrate in highly polar polymers such as poly(vinylpyrrolidone) and/or poly(acrylamide) can result in the formation of single-phase glassy solid materials, in which NH 4 (+) and NO 3 (-) are separated through an ion-dipole interaction with the polymer matrix. Below the glass transition temperature of the polymer matrix the resulting materials remain phase and thermally stable as demonstrated through the absence of decomposition as well as the solid-solid transitions and melting of ammoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…It is possible that if the amount of additives is large, perhaps the effects of hydrogen bonding are increased. In support of this, Lang and Vyazovkin [39] found that the phase stability of AN remained when the amount of polymer additive was much larger. Hence we thought that hydrogen bonding may play an important role in the interaction of ammonium ion with the additive.…”
Section: Dsc Analysismentioning
confidence: 82%
See 3 more Smart Citations
“…It is possible that if the amount of additives is large, perhaps the effects of hydrogen bonding are increased. In support of this, Lang and Vyazovkin [39] found that the phase stability of AN remained when the amount of polymer additive was much larger. Hence we thought that hydrogen bonding may play an important role in the interaction of ammonium ion with the additive.…”
Section: Dsc Analysismentioning
confidence: 82%
“…According to these results, the vibrations of NO 3 − were not changed. Comparative analysis of the IR spectra shown in Figure 9 reveals the disappearance of the bands at 3058 cm −1 associated with stretching vibrations of N−H bonds, suggesting that AN and PF maybe form a new system of hydrogen bonds in the mixture [12]. At the same time, the vibration frequencies of the ammonium ion at around 3200 cm −1 , remain virtually unchanged in the mixture.…”
Section: Ir Analysismentioning
confidence: 96%
See 2 more Smart Citations
“…Therefore, a great deal of research has been devoted to creating the so-called phase stabilized AN (PSAN) by mixing AN with additives from metal powder, metal oxides, carbonates, and related nitrates [4][5][6][7]. Recently, polymeric binders for stabilizing AN (suppression of AN phase transitions) were proposed with the objective of immobilizing ammonium NH 4 + and nitrate NO 3 ‾ ions within the polymeric matrix [8][9][10]. The chosen polymer should interact with ionic moieties (i.e., high dipole moment from a strong polar functional group) with a glass transition temperature (T g ) that is sufficiently high and potential candidates include poly (vinyl pyrrolidone):PVP and poly (acryl amide):PAM.…”
Section: Introductionmentioning
confidence: 99%